Food biochemistry and food processing - Simpson, Benjamin K. (Wiley-Blackwell, 2012)
The biochemistry of food is the foundation on which the research and development advances in food biotechnology are built. In Food Biochemistry and Food Processing, Second Edition, the editors have brought together more than fifty acclaimed academicians and industry professionals from around the world to create this fully revised and updated edition. This book is an indispensable reference and text on food biochemistry and the ever increasing developments in the biotechnology of food processing. Beginning with sections on the essential principles of food biochemistry, enzymology, and food processing, the book then takes the reader on commodity-by-commodity discussions of biochemistry of raw materials and product processing. Chapters in this second edition have been revised to include safety considerations and the chemical changes induced by processing in the biomolecules of the selected foodstuffs. This edition also includes a new section on health and functional foods, as well as ten new chapters including those on thermally and minimally processed foods, separation technology in food processing, and food allergens. Food Biochemistry and Food Processing, second edition fully develops and explains the biochemical aspects of food processing, and brings together timely and relevant topics in food science and technology in one package. This book is an invaluable reference tool for professional food scientists, researchers and technologists in the food industry, as well as faculty and students in food science, food technology and food engineering programs.- Resumé vydavatel
Keywords: potravinářství; analýza potravin; balení potravin; potravinářská biochemie; food industry and trade; food analysis; food packaging; food biochemistry; elektronické knihy; sborníky; electronic books; papers of several authors